Sacrificed Privacy: Criticism of Child Exploitation on Social Media from the Perspective of Maqasid al-Syariah - Mohammad Imamin Na'im; Nurmu’izzatin Zaharatul Parhi; Moh. Asyiq Amrulloh (The Indonesian Journal of Islamic Law and Civil Law, 2026)
The phenomenon of children being used as content on social media solely to pursue viewers has generated serious problems, as it neglects their fundamental rights. Based on this concern, this study aims to explain why children should not be exploited as content merely for social media viewers and to analyse it through the perspective of maqasid al-Syariah. The research employs a qualitative approach using the library study method. Data sources were obtained from books, journal articles, proceedings, research reports, and credible official websites, which were then analysed within the framework of maqasid al-Syariah. With its descriptive, analytical, and explorative character, this study does not only describe the practice of child exploitation on social media but also interprets its impact on the five fundamental principles of maqasid al-Syariah, namely religion, life, intellect, lineage, and property. The findings reveal that turning children into digital content clearly harms their best interests. Such practices violate the right to protection, cause psychological trauma, erode privacy, and shift the meaning of the parent–child emotional bond into that of a producer–actor relationship. The analysis of maqasid al-Syariah confirms that this phenomenon contradicts hifz al-nafs as it endangers life, hifz al-‘aql as it disrupts intellectual development, hifz al-nasl as it weakens the foundation of lineage, and hifz al-mal as financial motives cannot justify sacrificing a child’s dignity. Therefore, the exploitation of children in digital media has neither moral nor religious legitimacy. This research contributes to strengthening the conceptual basis for parents, policymakers, and industry actors to be more sensitive in protecting children in the digital sphere, while also enriching academic literature with a robust and applicable normative-religious framework.